Quo Vadis Kurikulum Keagamaan MAN Insan Cendikia Serpong: Ketika Prestasi Keagamaan Tidak Menjadi Prioritas di Madrasah Aliyah - Djaed, Rahadian Fatawi (Revorma: Jurnal Pendidikan dan Pemikiran, 2023)
This article aims to explore the crucial issue regarding the prioritization of religious education within the curriculum of Insan Cendikia Serpong Islamic High School. Its focus lies at the intersection of academic excellence and religious commitment. The research delves into the challenges faced when religious achievements do not take precedence in the context of Madrasah Aliyah. Through in-depth analysis and qualitative research methods, this article examines the implications of this shift in priorities and its impact on the overall religious education landscape. The study raises significant questions about the development of religious education in contemporary Islamic schools and triggers reflections on the fundamental goals and values that underpin educational institutions in shaping religious identity and academic excellence.